Children's Theology: Learning Media for Sunday School Children Using Book Creator in Indonesia - Tarigan, Yan Pratama; Simangunsong, Bestian; Sihombing, Warseto Freddy (LPPM IAKN Tarutung, 2023)
This research wants to develop learning media for Sunday school children who seem conventional towards digital by using Book Creator. This development arose due to the need to keep up with the times, create child-friendly churches, and maintain the quality of teaching to Sunday school children. However, churches tend to be lacking in preparing the quality of Sunday school learning media. The author observes that these problems can be overcome by developing learning media that suit the needs of Sunday school children. By paying attention to the needs of Sunday school children inseparable from the principles of theology in it, book creators are very appropriate in assisting educators to prepare quality learning. The hypothesis proposed is the basis of children's theology on Sunday school teaching materials and developing book creator-based Sunday school children's learning media so that they can produce ready-to-use digital products. The results show that teaching materials tend to be good theologically, and teaching materials need to be developed into book creators, so that educators can improve competence and students can understand God's Word through the use of technology. In the development stage, product validation results based on material, media, and language experts showed an average of 87.6% with the category